A comprehensive analysis of percutaneous liver biopsy characteristics and pathological manifestations in a large patient cohort (2009–2024) - Minling Cao; Jiayi Zeng; Jiayu Wang; Junmin Jiang (BMC Gastroenterology)
Abstract Objective This study aimed to analyze the characteristics of patients undergoing percutaneous liver biopsies and investigate the pathological manifestations of four major liver diseases across different age groups. Methods A retrospective analysis was conducted of 4,717 liver pathology reports from 2009 to 2024. The study population comprised 4,188 patients who underwent liver biopsies, with 408 patients receiving two biopsies and 50 patients who underwent three or more procedures. Most of biopsies (4,171) were performed between 2013 and 2023. Disease categorization, temporal distribution, and pathological manifestations across different age groups were assessed employed descriptive statistics, trend analyses, and graphical representations. Results Since 2020, a gradual increase has been observed in the proportion of cases involving concurrent hepatitis B complicated by metabolic-associated steatohepatitis (MASLD), along with an elevation in the incidence of MASLD alone. Pathological manifestations varied considerably across different age groups. Patients with hepatitis B complicated by MASLD exhibited disease exacerbation in middle age, with both liver inflammation and fibrosis grading worsening as age advanced. Furthermore, within the same age bracket, the severity of inflammation and the extent of fibrosis were more pronounced in cases where chronic hepatitis B was combined with MASLD compared to those with isolated chronic hepatitis B or MASLD. Conclusion This study offers a comprehensive analysis of the characteristics and pathological manifestations of patients who underwent percutaneous liver biopsies over a 15-year period. The findings underscore the varying pathological manifestations across different age groups for the four major liver diseases and emphasize the necessity for tailored therapeutic interventions, particularly for patients with concurrent hepatitis B and MASLD, as antiviral therapy alone may be inadequate. Further research is warranted to explore optimal management strategies for these patient subpopulations.